Genetic differentiation among Parastichopus regalis populations from Western Mediterranean Sea: potential effects of its fishery and current connectivity. - MAGGI, C.; GONZÁLEZ-WANGÜEMERT, M. (Mediterranean Marine Science, 2015)
<!– P margin-bottom: 0.08in; direction: ltr; color: rgb(0, 0, 0); line-height: 200%; widows: 2; orphans: 2; P.western font-family: "Calibri",sans-serif; font-size: 11pt; P.cjk font-family: "Calibri",sans-serif; font-size: 11pt; P.ctl font-family: "Calibri",sans-serif; font-size: 11pt; A:link color: rgb(0, 0, 255); –> Parastichopus regalis (Cuvier, 1817) is the most expensive seafood product on the catalonian market (NE Spain), with prices around 130 €/Kg (fresh weight). Despite its ecological and economic importance, biological and genetic information on this sea cucumber species is scarce. We provided the first insight on the genetic structure of P. regalis using sequences of cytochrome oxidase I (COI) and 16S genes, as well as a morphological description of its populations. Individuals were collected in six locations along the Spanish Mediterranean coast, including an area under fishery pressure (Catalonia). We found high haplotype diversity and low nucleotide diversity for both genes, with higher levels of genetic diversity observed on COI gene. Population pairwise fixation index (FST), AMOVA and correspondence analysis (CA) based on COI, revealed significant genetic differentiation among some locations. However, further analysis using nuclear markers (e.g. microsatellites) would be necessary to corroborate these results. Moreover, the genetic and morphological data may indicate fishery effects on the Catalonian population with decrease of the size and weight average and lower genetic diversity compared to locations without fishery pressure. For an appropriate management of this species, we suggest: 1) an accurate assessment of the stocks status along the Spanish coasts; 2) the study of the reproductive cycle of this target species and the establishment of a closed fishery season according to it; 3) the founding of protected areas (i.e. not take zones) to conserve healthy populations and favour the recruitment on the nearby areas.